Situation Report: Bulgaria, 16 September 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Regional System Introduced / by Stephen Ashley Problems and Controversies over the New Regional System / by Stephen Ashley Mitko Grigorov, Former Chief Ideologist, Dies at the Age of 66 / by Rada Nikolaev